Alizarin and Chrysazin Inhibit Biofilm and Hyphal Formation by Candida albicans - Manoharan, Ranjith Kumar; Lee, Jin-Hyung; Kim, Yong-Guy; Lee, Jintae (Frontiers in Cellular and Infection Microbiology, 2017)
Candida albicans is one of the most common pathogen causes fungal infections. This opportunistic pathogen can form biofilms comprised of yeast, hyphae and pseudo hyphal elements, and the hyphal form C. albicans considered as probable virulence factor. We investigated the antibiofilm activities of 13 quinones and anthraquinones related compounds against C. albicans biofilms by using crystal violet and 2,3-bis (2-Methoxy-4-Nitro-5-Sulfo-phenyl)-2H-Tetrazolium-5-Carboxanilide (XTT) reduction assays to assess inhibitions of biofilm growth. Morphological changes in biofilms and biofilm thicknesses were determined by scanning electron microscopy and confocal laser scanning microscopy, respectively. It was found alizarin (1,2-dihydroxyanthraquinone) and chrysazin (1,8-dihydroxyanthraquinone) suppressed C. albicans biofilm formation. Interestingly, alizarin and chrysazin at only 2 µg/ml effectively inhibited hyphal formation and prolonged the survival of C. albicans infected Caenorhabditis elegans, thus showing a distinct antivirulent potential. A structural activity relationship study of alizarin and 6 other anthraquinones showed the presence of a hydroxyl group at C-1 position which is important for antibiofilm and antifilamentation activities. Transcriptomic analyses revealed that alizarin downregulated the expression of several hypha-specific and biofilm related genes (ALS3, ECE1, ECE2 and RBT1). Furthermore, unlike the commercial antifungal drug fluconazole, no acute toxic effect was observed when uninfected nematodes were exposed to alizarin at concentrations up to 1 mg/ml. The results of this study indicate alizarin suppresses the virulence of C. albicans in vivo which suggests alizarin may be considered as a potential candidate for further investigations to develop antifungal agent against fungal pathogen in vivo.